Adolescents with acute lymphoblastic leukaemia: emerging from the shadow of paediatric and adult treatment protocols. - Ramanujachar, R; Richards, S; Hann, I; Webb, D (2006)
Adolescents and young adults (AYA) with acute lymphoblastic leukaemia (ALL) constitute a distinct population from children and older adults. Based on patterns of referral, they may be treated by either paediatric or adult oncologists. As a group, AYA with ALL have a worse survival and event-free survival (EFS) compared to that achieved by younger children. A systematic review of all published clinical trials, which provide data on treatment and outcome of adolescents with ALL, has been summarised in an effort to determine whether they should be treated on paediatric or adult type protocols. Adolescents appear to have a consistent survival advantage when treated on paediatric regimens.